2005
DOI: 10.1002/app.22557
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of biodegradable poly(propylene carbonate)/wood flour composites

Abstract: Wood flour reinforced poly(propylene carbonate) (PPC) composites were prepared by melt blending followed by compression molding. The effects of reinforcement on the morphology, static and dynamic mechanical properties, and thermal properties of PPC/wood flour composites were investigated. In terms of mechanical properties, wood flour had the significant effect of improving tensile strength and stiffness. Scanning electron microscopic examination revealed good dispersion of wood flour (especially at lower conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 94 publications
6
21
0
Order By: Relevance
“…Therefore, it is evident that low loading of PDA not only effectively improves thermal stability but also improves T g to an extent which maleic anhydride cannot do. [15] 30 36 42 Wood flour [17] 40 43.8 53.7 Graphene oxide [10] 1 29 39.5 Modified graphite oxide [11] 5 30.6 42.2 Maleic anhydride [7] 2 43.7 46.6 PDA 1 44.85 54.50…”
Section: Glass Transition Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is evident that low loading of PDA not only effectively improves thermal stability but also improves T g to an extent which maleic anhydride cannot do. [15] 30 36 42 Wood flour [17] 40 43.8 53.7 Graphene oxide [10] 1 29 39.5 Modified graphite oxide [11] 5 30.6 42.2 Maleic anhydride [7] 2 43.7 46.6 PDA 1 44.85 54.50…”
Section: Glass Transition Temperaturementioning
confidence: 99%
“…In order to reinforce PPC, some researchers incorporated fillers, such as graphene oxide [10,11] and organophilic montmorillonite [12] into PPC. Besides, additives or fillers containing a large amount of proton donors, such as urethane [13] , o-lauroyl chitosan [14] , starch [15] and starch acetate [16] , wood flour [17] , succinic anhydrate [18] and hyperbranched poly(ester-amide) [19] , were utilized to perform hydrogen bonding with PPC which would improve the thermal stability and/or mechanical properties. Nevertheless, it still remains a great challenge to achieve the goal of significantly improving the thermal stability and mechanical properties under the premise of maintaining environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…The scanning electron microscopy studies on PPC/MBS blends showed that MBS particles were dispersed well in the PPC matrix when MBS content was 1 3 networks (PIPPCNs) by terpolymerization to enhance the thermal stability of PPC. Many studies have focused on PPC blended with different types of fillers such as organophilic montmorillonite (OMMT) [15], wood flour [16] and ZnO [17] to enhance the mechanical properties and T g of PPC. PPC has also been blended with polymers such as poly(lactic acid) (PLA) [18], poly(3-hydroxyvalerate-co-3-hydroxyvalerate) (PHBV) [19] and poly(1,2-propylene succinate) (PPSu) [20] to make PPC an applicable material at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the as-synthesized PPC is still far from practical application, and it should be reinforced to extend its applications [8]. A lot of works, including chemical and physical attempts [9][10][11][12][13][14][15][16][17][18][19][20], have been done to modify the material profile of pure PPC by blending with polymers or fillers. However, they all show a very limited improvement for the investigated compounds using PPC as the dominant component (e.g., yield stress ratio of composite and matrix is less than 2 when the content of additives is less than or equal to 5 wt%).…”
Section: Introductionmentioning
confidence: 99%
“…The additives in composite from A to I are ethylene vinyl alcohol, wood flour, starch, natural fiber, 1,6-bis(hydroxyisopropyl urethane)hexane, glass fiber, polylactic acid, graphite oxide and organophilic montmorillonite, respectively (Refs [11][12][13][14][15][16][17][18][19]…”
mentioning
confidence: 99%